Association of hospitalist presence and hospital‐level outcome measures among medicare patients. Issue 1 (27th November 2013) - Jungerwirth, Robert; Wheeler, Stephanie B.; Paul, John E.
<x xml:space="preserve">Abstract</x> BACKGROUND Hospitalists have been shown to lower patient costs through better resource utilization and decreased length of stay, but it is unclear whether hospitalists are associated with quality of care. We examined the association between the presence of hospitalists and 30‐day predicted excess all‐cause hospital mortality and readmissions among Medicare patients admitted to a hospital with any of 3 conditions: heart failure, acute myocardial infarction, and pneumonia. METHODS Using national hospital‐level, case mix‐adjusted, risk‐standardized, 30‐day all‐cause excess mortality and readmission data from the Centers for Medicare and Medicaid Services, we used descriptive and bivariate statistics to illustrate trends across hospitals. Using multivariable ordinary least squares regression to control for hospital‐level characteristics, we then estimated the association between the presence of hospitalists and predicted hospital mortality and readmission. RESULTS After multivariable adjustment, the presence of hospitalists was associated with lower probability of readmission for all 3 target conditions. No significant associations for any of the target conditions were found in all‐cause mortality models. CONCLUSIONS Hospitalists are already integral to the delivery of inpatient care at most institutions. This study, however, showed an association at the national level of the presence of hospitalists with an important and timely quality measure: reduction of readmission rates. Future research is indicated to explore specific causation pathways for the impact of hospitalists on quality of care. Journal of Hospital Medicine 2014;9:1–6. © 2013 Society of Hospital Medicine